LITERATURE STUDY OF L-CARNITINE PREPARATION METHODS FOR 1000 TONS OF ANNUAL PRODUCTION - Annida Khoirun Nisa Purwadini; Cucuk Evi Lusiani (DISTILAT: JURNAL TEKNOLOGI SEPARASI, 2022)
L-carnitine is a gamma-hydroxy amino acid and also known as vitamin Bγ. L-carnitine has many benefits as well as uses. Supplements with L-carnitine content are much needed in the field of health. L-carnitine is obtained using a variety of methods. They are the chemical optic resolution method, the biological method, and those that use chiral materials from natural sources. The purpose of this literature study is to determine the best method to be used in the design of the L-carnitine production plant with a capacity of 1000 tons per year by comparing various existing methods from various aspects. Based on the results of the comparison, it was found that the production of L-carnitine from (S)-3-activated hydroxybutyrolactone is the best method to be used in the production of L-carnitine capacity of 1000 tons per year for 300 days. This method produces a lot-more L-carnitine products at a lower cost than other methods that have a higher yield.